Fatigue is associated with worse cognitive and everyday functioning in older persons with HIV. (6th January 2022) - Campbell, Laura M.; Sun-Suslow, Ni; Heaton, Anne; Heaton, Robert K.; Ellis, Ronald J.; Moore, David J.; Moore, Raeanne C.
Abstract : Objective: The aim of this study was to determine whether there are relationships between fatigue, cognition, and everyday functioning in older persons with and without HIV and to examine if associations remain after accounting for depression, anxiety, and sleep quality. Methods: Sixty-nine persons with HIV (PWH) and 36 persons without HIV, aged 50–74 years, were recruited from ongoing studies at UC San Diego's HIV Neurobehavioral Research Program and from the community. Participants completed neuropsychological testing, a performance-based measure of everyday functioning, and self-report questionnaires of fatigue, depression, anxiety, sleep quality, and everyday functioning. Multivariable linear regressions and logistic regressions stratified by HIV serostatus were used to examine relationships between fatigue, cognition, and everyday functioning. Psychiatric symptoms and sleep quality were examined as covariates. Results: In this cross-sectional study, PWH had significantly greater fatigue than the HIV-negative group ( g   =  0.83; P  < 0.01). When stratifying by HIV serostatus, greater fatigue was significantly associated with worse global cognition ( β  = −0.56; P  < 0.01) in PWH even when controlling for covariates;however, fatigue was not significantly associated with global cognition in persons without HIV. In PWH and when accounting for covariates, fatigue was also associated with greater risk of self-reported everyday functioning impairment [odds ratio (OR) = 1.66 for 10-point increase in fatigue, P   =  0.04] but not performance-based everyday functioning ( P  = 0.95). Conclusion: Fatigue is associated with cognition, particularly measures with a speeded component, and self-reported everyday functioning in older PWH. Findings suggest that fatigue is important to assess and consider in the context of aging with HIV.